Near Field Focused Microstrip Patch Antenna Array Characteristics Enhancement With Parasitic Patch Elements - Sohail, Muhammad; Uyguroglu, Rasime (IEEE, 2021)
Several applications require a limited spot size and highly concentrated radiated electromagnetic waves from antenna arrays. In this study, we designed a near field focused rectangular microstrip patch antenna array with stacked parasitic patch elements to improve the focusing characteristics. The parasitic elements are driven by the conventional near field focused array and the radiated fields are intensified at the focal point, while preserving the basic focusing characteristics of patch antenna array. The designed parasitic patch antenna array raises the power level at the focal point by about 4.2 dB as compared to conventional near field focused patch antenna array. The designed antenna array provides a focused high power radiated fields to be used for different applications such as biomedical, industrial and short range wireless power transfer.
29th IEEE Conference on Signal Processing and Communications Applications (SIU) -- JUN 09-11, 2021 -- ELECTR NETWORK
Keywords: Near Field; Field Focusing; Patch Antenna Array; Parasitic Patch